Sebaran Ruang Terbuka Hijau dan Peluang Perbaikan Iklim Mikro di Semarang Barat - Dewi Liesnoor Setyowati; Sri Mantini Rahayu Sedyawati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2010)
The purpose of the research was detecting green open space (GOS) spread and micro climate condition at Semarang Barat, with vegetation spread and street lane area as the object of the research. Population characteristic consisted of vegetation area spread, mainly on the shaded trees composition and micro climate condition by using purposive sampling technique. The research used descriptive ecologycal approach. The result described that Semarang Barat vegetation spread is included as sparse vegetation, predominantly by squat vegetation composition with infrequent tree density. Micro climate conditon is categorized as contented climate, but on edge at the daylight. The condition is infl uenced by least along the street; consequently the micro climate of temperature is high with low humidity. Semarang Barat GOS is 17,1%, so the spacious should be 10,0% enhanced to gain 27,1% GOS to create a better climate. It is suggested to increase squat vegetation composition and quantity along Semarang Barat streets, so vegetation diversity will recovered.Keywords: green open space, micro climate, Semarang Barat